Aplikasi edible coating dengan ekstrak rambut jagung pada buah stroberi - Zahra Widya Putri; Hasya Nurfauziyyah; Helen Kristina Putri; Imas Masto’ah; Fadilla Al Azqia; Desy Triastuti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Edible coating on strawberries is a technology that involves applying a thin layer to the surface of strawberries to slow respiration, retain moisture, and prevent contamination. Corn silk is waste that contains active compounds such as phenols, glycosides, and saponins, which have antibacterial properties. This study aimed to determine the effect of using corn silk extract as an antibacterial agent in edible coatings on the physicochemical characteristics of strawberries during storage. The study design used was a Complete Randomized Design with factors of corn silk extract concentration (0, 0.5, 1, and 1.5%) and storage temperature (27, 4, and -18°C. The results showed that the concentration of corn silk extract in edible coating did not significantly affect the physicochemical characteristics of strawberries, but the storage temperature significantly affected the weight loss, hardness, and vitamin C content. Room temperature storage showed more quality deterioration, chilling storage had the lowest average weight loss of 25.85% and the highest TSS of 12.74 °Brix, while freezer storage had the highest values for vitamin C, Total Titratable Acidity, hardness, and color parameters.